STRATEGI PERCEPATAN PENURUNAN STUNTING: STUDI KASUS, PENDAMPINGAN AKSI CEGAH STUNTING DI KELURAHAN RAWANG - Januardi; Fitriati; Yonny Arita Taher; Asnawilis; Silvia Millenia Afrila; Jefri Gusnedi; Finicho Yulandra; Supriadi (LPPM Universitas Ekasakti, 2024)
From the result of the survey that we onduted and the data House Of KB Bukit Karan village loated in Rawang village, south Padang district, we found a health problem for hildren under the age five years (toddlers), namely the number of children who still economic factors, factors of law education levels that make human resaues law, the method in this study is qualitative and the implemention of activities with a learning approach in the from of training. The result of the training process are, first, to produk an Kampung KB Bukit Karan, Rawang Village, South Padang District, Seond, to increase public Kampung KB Bukit Karab, Rawang Village, South Padang.